Pension coverage for parents and educational investment in children: Evidence from urban China - Ren Mu; Yang Du (Institute for the Study of Labor (IZA), 2012)
When social security is established to provide pensions to parents, their reliance upon children for future financial support decreases; and their need to save for retirement also falls. We use the expansion of pension coverage from the state sector to the non-state sector in urban China as a quasi-experiment to analyze the intergenerational impact of social security on educational investments in children. With a difference-in-differences framework, we find a significant increase in the total education expenditure attributable to pension expansion. The results are unlikely to be driven by trends in medical insurance, wages, bonus income, and housing values. They are robust to the inclusion of a large set of control variables and to different specifications, including one based on the instrumental variable method.
Keywords: J26; J24; O15; D13; 330; pension; education expenditure; gender difference; urban; China